Age-Related Peculiarities of Glutathione Antioxidant System Dynamics in Response to Cranio-Skeletal Trauma and Effectiveness of Cell Therapy - Y. Sushko (Львівський клінічний вісник)
Introduction. In the modern urbanized society, people of all age groups are at high risk of suffering from combined cranio-skeletal trauma (CST). Oxidative stress plays a key role in the pathogenesis of CST. Reduced glutathione (GSH) is one of the antioxidants that prevents the formation of free radicals. In order to prevent secondary damage to the brain and internal organs in the case of trauma, the effect of cell therapy is being actively studied.